Spectroscopic evidence in solid and solution of a discrete copper(I) tetrahedral complex dimer supported by supramolecular interactions - Jara, Danilo H. (2012)
The first study of the self-association of a copper(I) tetrahedral complex ([Cu(N-{4-nitrophenyl}pyridine-2-yl-methanimine)(PPh 3)Br]) has been performed. The formation of a discrete dimer supported by supramolecular π-π stacking and C-H·Br interactions was established by X-ray diffraction techniques. 1D- and 2D NMR techniques were used for the structural characterization of this compound in solution. Unexpected 1H- 1H NOE effects are coherent with the presence of a dimer in solution, whose structure replicates that found in the crystal. Dimerization constants obtained by VT- 1H NMR spectroscopy allowed the determination ofthe thermodynamic parameters for the self-association process, namely ΔS = -0.67±0.21 calmol -1K -1, ΔH = -2.00±0.05 kcalmol -1 and ΔG(298 K) = -1.79 kcalmol -1. Consequently, this association process is enthalpy driven.